PENGARUH STRATEGI PROMOSI, KUALITAS LAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI KAFE A SIXTY NINE COFFEE JAKARTA SELATAN - Budi Rahmat Halawa (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of promotional strategy, service quality, and product quality on purchasing decisions at A Sixty Nine Coffee, South Jakarta. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to consumers of A Sixty Nine Coffee who had previously made purchases. The sampling technique used was purposive sampling, with respondents selected based on predetermined criteria. The collected data were analyzed using multiple linear regression analysis with the assistance of statistical software. Prior to hypothesis testing, the data were examined through validity and reliability tests, as well as classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results of the study indicate that, partially, promotional strategy has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, and product quality has a positive and significant effect on purchasing decisions at A Sixty Nine Coffee, South Jakarta. Based on these findings, it can be concluded that effective promotional strategies, optimal service quality, and high product quality play an important role in enhancing consumers’ purchasing decisions.